Bordering neighbours: Testing for border effect on Malaysia's northern states and Southern Thailand - Muzafar Shah, Habibullah; Dayang Affizzah, Awang Marikan (Munich University Library, 2008)
Economists agree that countries that are close together may experience common shocks that affect growth; that a country’s growth rate depends not only on domestic investment but also on the investment of its neighbouring countries. On the negative point, common shock such as wars and political instability can also have an adverse effect on growth of neighbouring countries. First, regional instability disrupts trade flows. Second, regional instability forces increases in military outlays, and will have a negative effect on economic performance. The purpose of the present study is to determine whether the growth rate of the neighbouring provinces of Southern Thailand has an effect on the economic growth of the Northern states of Malaysia. Using annual data from 1983 to 2003, our results using the long-run Granger causality in the vector error correction model setting suggest that Songkhla and Yala Granger cause Kedah; Songkhla Granger cause Perlis; and Narathiwat Granger cause Kelantan. On the other hand, while Perak and Yala indicate Granger cause in both direction, Perlis and Satun are independent of each other.